Influence of presence or absence of keratinized mucosa on the alveolar bony crest level as it relates to different buccal marginal bone thicknesses. an experimental study in dogs - Bengazi, Franco; Botticelli, Daniele; Favero, Vittorio; Perini, Alessandro; Urbizo Velez, Joaquin; Lang, Niklaus P. (Wiley, 2013)
Objective: To investigate the influence of the presence or absence of keratinized mucosa on the alveolar bony crest level as it relates to different buccal marginal bone thicknesses. Material and methods: In six beagle dogs, the mandibular premolars and first molars were extracted bilaterally. In the right side of the mandible (test), flaps were elevated, and the buccal as well as part of the lingual masticatory mucosa was removed. The flap was released coronally to allow a primary wound closure. In the left side, the wounds were left unsutured with the keratinized mucosa remaining (control). After 3 months of healing, a complete absence of keratinized mucosa was found at the test sites. Two recipient sites were prepared at each side of the mandible, one in the premolar and one in the molar region. A buccal bony ridge width of approximately 1 and 2 mm was obtained at the premolar and molar region, respectively. Implants were installed with the shoulder flush with the buccal alveolar bony crest, and abutments were connected to allow a nonsubmerged healing. At least 2 mm of keratinized mucosa was surrounding the control sites, while at the test sites, the implants were bordered by alveolar mucosa. After 3 months, the animals were euthanized and ground sections obtained. Results: A higher vertical bony crest resorption was observed at the test compared with the control sites both at the premolar and molar regions, the differences being statistically significant. The top of the peri-implant mucosa was located more coronally at the control compared with the test sites. The horizontal resorption measured 1 mm below the implant shoulder was similar at the test and control sites. Only limited differences were found between premolar and molar sites, with the exclusion of the horizontal resorption that was higher at the test compared with the control sites. Conclusions: A higher alveolar buccal bony crest resorption and a more apical soft tissue marginal position should be expected, when implants are surrounded with thin alveolar mucosa at the time of installation, independently of the thickness of the buccal bony crest. © 2013 John Wiley & Sons A/S.
Keywords: Alveolar bony crest; Alveolar mucosa; Animal study; Histometry; Keratinized mucosa; Wound healing